THE EFFECT OF OWNERSHIP STRUCTURE ON AUDIT QUALITY IN THE BANKING SECTOR IN 2010-2018 - Evelyn Christina Kurniawan (Jurnal Ekonomi, 2023)
This study aims to identify the effect of state ownership structure and large share ownership on audit quality in the banking sector. The sample for this research is banking sector companies listed on the Indonesia Stock Exchange (IDX) in 2010-2018. Researchers used the ordinal logistic regression test, model testing was done twice. The first study measured large shares with a concentration of ownership of the first 10 shareholders. The second research measures large shares with block share ownership above 5%. The results of the study show that there is no significant effect between state ownership and ownership concentration variables on audit quality. The results of the study used a robust blockholder ownership variable in the first study. This can be explained by the characteristics of market players in Indonesia, most of whom only consider capital gains and pay little attention to audit quality. The conclusion of this study is that the role of governance is less than optimal in the banking sector in Indonesia. This research can be useful for evaluating the implementation of governance regulations and evaluating bank audit quality.